I am Princess X - Priest, Cherie; Ciesemier, Kali (2015)
Years after writing stories about a superheroine character she created with a best friend who died in a tragic car accident, sixteen-year-old May is shocked to see stickers, patches, and graffiti images of the superheroine appearing around Seattle.
Ages 12-15.
Keywords: Women superheroes -- Juvenile fiction; Webcomics -- Juvenile fiction; Friendship -- Juvenile fiction; Seattle (Wash.) -- Juvenile fiction; Electronic books